First measurement of the CP-violating phase ϕdd¯¯¯sϕsdd¯ in B s 0 → (K+π−)(K−π+) decays; Journal of High Energy Physics; Vol. 3 - Aaij R.; Panshin G. L. Gennady Leonidovich; Strokov S. A. Sergey Aleksandrovich; Vagner A. R. Aleksandr Rudolfovich (2018, 2018)
Title screen